APLIKASI KONVERSI BASISDATA RELASIONAL MYSQL KE ONTOLOGI SEBAGAI BASIS PENGETAHUAN APLIKASI BERBASIS WEB SEMANTIK - Andri, Andri (Universitas Bina Darma, 2012)
Before the development of semantic web technologies, a variety of applications using web technologies are still many who use a relational database as a representation of the stored data. So if there are those who want to develop semantic web technology that uses ontologies as a metadata web will experience some difficulties if you have to use the old data. In this study will be make a conversion application a relational database MySQL to the ontology as a knowledge base that can be used in semantic web applications based. This application is designed to facilitate the development of semantic web application that uses data from the relational database sources in order to facilitate the development of semantic web-based applications. In making this conversion application to use a programming language Java is an object-oriented programming language. Keywords: Semantic Web, Convertion, Database, MYSQL, Ontology, Java